(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The inhibitory effect of aqueous garlic extract (AGE) against clinically significant microorganisms including Candida species is documented. The activity and stability of this extract in topical pharmaceutical formulations has received little attention. This communication reports on the stability and anticandidal activity of AGE in gel and lotion formulations. Gel and lotions containing 50, 100 and 200 mg garlic/ml were prepared and their physical as well as biological stability was established at 40ºC. The anticandidal effect of all preparations was determined using the well diffusion method and Muller Hinton agar. Results indicated that both of the prepared formulations were physically stable but the freshly prepared lotion exhibited no anticandidal effect. Gels were effective inhibitors but this activity was lost with storage at 40ºC in less than 9 days. It is concluded that lotion was not at all a suitable delivery system for AGE as it lost its activity during preparation. Whereas, freshly prepared gels were good inhibitors but this property was diminished upon storage. Comprehensive studies are needed to stabilize the AGE gel formulation over the expected shelf life.